The Role of Nanomaterials in Preventive Dentistry: Antimicrobial Coatings for Dental Restorations: Nanomaterials in Preventive Dentistry: Antimicrobial Coatings - Sohail, Shahneela; Sadiq, Rabia; Tasleem, Farah; Kumar, Naresh; Imtiaz, Ayesha; Zeeshan, Muhammad; Ali, Fatima (Pakistan Journal of Health Sciences, 2024)
The applicability of antimicrobial nanomaterial coatings in preventive dentistry such as dental restoration practice in combating dental caries while embracing biocompatibility, and long-lasting and low bacterial adhesion properties has been the main area of research for many decades. Objective: To review the role of different types of nanomaterials in the field of preventive dentistry by focussing on anti-microbial coatings for dental restorations. Methods: The articles were taken from PubMed, Science Direct, and Google Scholar within the years 2018-2024 following PISMA 2020 guidelines. The effectiveness of nanomaterials included in dental coatings in terms of antimicrobial properties, biocompatibility, and durability in clinical applications was observed. Bacterial adhesion, caries prevention, material nanotechnology, and patient satisfaction were assessed. The antimicrobial efficiency and restorative outcomes of different nanomaterials: via silver, zinc oxide and titanium dioxide; were evaluated. Initially, 109 articles were retrieved, which were then screened based on predefined inclusion and exclusion, resulting in 16 studies for detailed analysis. The regions of study conduction were North America, Europe and Asia. Results: The antimicrobial efficacy of nano-coatings in dental restorations was seen via reduced bacterial adhesion and biofilm. The link between nanomaterials like silver nanoparticles and titanium dioxide enhanced secondary caries prevention and improved the long-term stability of restorative materials. Biocompatibility studies demonstrated that these coatings are biocompatible; however, more work is required. The application of antimicrobial nano-coatings gives adaptive and therapeutic characteristics. Conclusions: It was concluded that nanotechnology should lead to better durability and performance of dental restorations thus better oral health and less caries